The State of The World's Children 2013 : (UNICEF, 2013)
One in every seven children is disabled. Children with disabilities are among the most likely to be marginalized, poor and vulnerable. UNICEF is committed to improving the lives of children, particularly those who face the greatest disadvantages. The report will investigate the web of barriers disabled children face: discrimination, harmful norms and the lack of accurate information. The report will analyze and provide good-practice guidance on: inclusive health and education; prevention; nutrition; protection from violence, exploitation and abuse; emergency response; institutionalization; and the role of appropriate technology and infrastructure.